2019
DOI: 10.29356/jmcs.v54i4.919
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and Antioxidant Effects of Subcoriacin in Normal and Streptozotocin-induced Diabetic Rats

Abstract: Subcoriacin (1) is a 3-aryl-6-prenylcoumarin isolated from Eysenhardtia subcoriacea that has shown antioxidant activity in vitro, and has shown to scavenge free radicals and also to improve the reduced glutathione levels in pancreatic homogenates. The present investigation evaluates the protective effect of 1 against oxidative injury in normal and streptozotocin (STZ)-induced diabetic rats. The i.p. administration of 1 at a dose of 100 mg/kg body weight for 5 d, significantly decreased blood glucose levels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Diabetes mellitus is currently a major public health concern, because its incidence and prevalence are elevated and increasing, reaching epidemic proportions. 27 Cumulative evidence has shown that poorly and erratically controlled hyperglycemia produces abnormally high levels of ROS, 28 and these reactive substances could react with essential molecules such as lipids, proteins and DNA, leading to histological changes as well as functional alterations. 29 Diversity of medicinal plants and spices containing various phytochemicals with biological activity serve as viable source of drugs for the world population.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is currently a major public health concern, because its incidence and prevalence are elevated and increasing, reaching epidemic proportions. 27 Cumulative evidence has shown that poorly and erratically controlled hyperglycemia produces abnormally high levels of ROS, 28 and these reactive substances could react with essential molecules such as lipids, proteins and DNA, leading to histological changes as well as functional alterations. 29 Diversity of medicinal plants and spices containing various phytochemicals with biological activity serve as viable source of drugs for the world population.…”
Section: Discussionmentioning
confidence: 99%
“…STZ induced hyperglycemia in models was previous used" by Vasconcelos et al [101]. STZ induces hyperglycemia in experimental animals and used to induce diabetes in rats" [102]. "Intraperitoneal injection of STZ increased plasma glucose level gradually to reach its maximum level within 14 days.…”
Section: Chemical Analysis Of Coriander (C Sativum) Extractmentioning
confidence: 99%